THE EFECTS OF COGNITIVE REMEDIATION THERAPY IN BIPOLAR DISORDER PATIENTS - Cahya Pandya Astami (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Background: Bipolar Disorder (BD) is a mental disorder impacting 45 million people worldwide. BD patients often experience persistent cognitive impairments. These cognitive impairments can impact psychosocial outcomes and reduce employment. Cognitive remediation (CR) is a behavioral training-based intervention that points to help cognitive processes and improve functional outcomes. The effects of CR in BD are inconclusive. Some studies claimed that CR could improve many cognitive domains and increase Quality of Life, but other study claims that CR didn't improve overall cognitive and psychosocial functioning. In this paper, we aim to explore the effect of CR in BD patients. Objective: To understand the effects of cognitive remediation therapy in bipolar disorder patients. Methods: The author tried to explore all the papers in English published from 2018 to 2022. The electronic databases used are Google Scholar, ScienceDirect, Elsevier, Wiley Library, PubMed, and Cochrane. Two sets of keyword search algorithms were used with Boolean operator AND. The first keyword was